Efeitos da prática da ioga no controle postural e bem estar de trabalhadores - Santos, Kleber Luís Silva dos (2013)
Workers quality of life is a very important aspect to be considered by both health professionals and executives and the Yoga practice can contribute in this context. Therefore the aim of this study is to identify the effects of a Yoga intervention program onpostural control and well-being of healthy workers.The effects of Yoga on different physical and mental health conditions werereviewed in the first part of thisstudy. Then an experimental study was conducted with twenty-four healthy workers from the same company as volunteers. Two groups were distinguished, one as experimental group, which engaged in a program of 16 Yoga classes (each class with 60 minutes of duration) at the company twice a week, and the other as control group.The effects of Yoga practice were evaluated through the Nordic Musculoskeletal Questionnaire and Work & Well-Being Survey Questionnaire (UWES 17) . The degree of postural stability was evaluated by a force plate and the center of pressure was the studied variable. After the intervention only the experimental group showed significantly improvements in musculoskeletal conditions and working engagement. Additionally significantly lower oscillation areas and center of pressure mean velocities were observed only for the experimental group. We conclude that the Yoga practice has improved musculoskeletal complaints and wellness in the workplace, as well as the sensory integration of the healthy workers.